1, 3-Dipolar cycloadditions with azomethine ylide species generated from aminocyclopropanes. Issue 38 (20th September 2018) - Wolan, Andrzej; Kowalska-Six, Justyna A.; Rajerison, Holisoa; Césario, Michèle; Cordier, Marie; Six, Yvan
Abstract: Two types of bicyclic N -cyclopropyl glycine ester derivatives have been prepared and put under scrutiny as possible precursors of azomethine ylides. The results demonstrate that they can indeed participate in 1, 3-dipolar cycloaddition reactions with dipolarophiles, as illustrated in the cases of phenyl vinyl sulfone, N -phenylmaleimide, diethyl fumarate and diethyl maleate. The relative configurations of the major diastereoisomers produced are consistent with the predicted generation of azomethine ylide species, reacting in concerted cycloaddition processes. This unprecedented way of generating such 1, 3-dipoles provides access to functionalised pyrrolizidine and pyrrolidine derivatives, that would be difficult to make directly by more classic methods. It was also found that using phenyl vinyl sulfone or N -phenylmaleimide as the dipolarophile reactant, a domino nucleophilic conjugate addition/1, 3-dipolar cycloaddition process may operate competitively. Graphical abstract: Image 1